2018
DOI: 10.5774/48-0-279
|View full text |Cite
|
Sign up to set email alerts
|

Movement in the Afrikaans left periphery: a view from anti-locality

Abstract: It has been convincingly argued that the so-called "left periphery" of the sentence makes available multiple positions which host topicalised and focalised phrases, among other elements. Projections in the C-domain have been shown to have a fixed ordering, the violation of which results in ungrammaticality. Rizzi (1997) provides a template that specifies this ordering. Botha and Oosthuizen (2009) examine this template's ability to account for ordering phenomena in the Afrikaans left periphery and make certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…An L1 comparison group in Roberts and Felser (2011) failed to show the effect on either stimulus region. In addition, Berghoff (2020) observed a prolonged processing effect among a childhood L2 group, with longer reading times on two post-critical words (and no effect on the critical noun itself). The L1 group in that study also showed a prolonged effect over the same two stimulus regions as did the L2 group, although the numerically longer reading times were only marginally significant on the second post-critical word with the L1 group.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…An L1 comparison group in Roberts and Felser (2011) failed to show the effect on either stimulus region. In addition, Berghoff (2020) observed a prolonged processing effect among a childhood L2 group, with longer reading times on two post-critical words (and no effect on the critical noun itself). The L1 group in that study also showed a prolonged effect over the same two stimulus regions as did the L2 group, although the numerically longer reading times were only marginally significant on the second post-critical word with the L1 group.…”
Section: Discussionmentioning
confidence: 91%
“…Another difference between that investigation and the present one was that the linguistic stimuli for that study manipulated the semantic plausibility of the post-verbal noun phrase as an object (e.g., As the men drank the song … versus As the men drank the beer …; Roberts and Felser, 2011 ) to create conflict with the processing principle of Late Closure, whereas the present study manipulated the transitivity of the verb. Berghoff (2020) compared the early Afrikaans-English bilinguals to late English-Afrikaans bilinguals and both groups showed the expected reading time increases on a post-verbal noun phrase that was implausible as a direct object of the verb versus a noun phrase that was a plausible object. In other words, they appeared to rapidly integrate verb argument specifications during online processing.…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations